The Influence of Financial Literacy, Age, and Income on the Financial Behavior of Tokopedia Customers - Aprisanty Aprisanty; Yeni Ariesa; Juli Meliza (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to investigate how Tokopedia users in Medan City behave financially in relation to their age, income, and level of financial knowledge. The Structural Equation Modeling-Partial Least Squares (SEM-PLS) analytical method is used in this quantitative study. One hundred respondents who shop on Tokopedia in Medan were given questionnaires in order to collect data. The findings show that while age has no discernible effect on financial behavior, income and financial knowledge do. Age, income, and financial literacy all account for 89.4% of the variation in financial behavior, according to the R-Square value of 0.894. These results demonstrate how better income management and financial literacy can assist people in making more informed financial decisions. To improve the community's financial well-being, effective income management techniques and financial education are crucial.